Study of the Seismic Response on the Infill Masonry Walls of a 15-Storey Reinforced Concrete Structure in Nepal - André Furtado; Nelson Vila-Pouca; Humberto Varum; António Arêde (Buildings, 2019)
Following the strong earthquake on April 25, 2015 in Nepal, a team from the University of Porto, in collaboration with other international institutions, made a field study on some of the most affected areas in the capital region of Kathmandu. One of the tasks was the study of a high-rise settle of buildings that were damaged following the earthquake sequence. A survey damage assessment was performed to a 15-storey infilled reinforced concrete structure, which will be detailed in the manuscript. Moreover, ambient vibration tests were carried out to determine the natural frequencies and corresponding vibration modes of the structure. The main aim of this manuscript is to present a numerical study concerning the influence of the masonry infill walls in the structure seismic response. For this, three numerical models were built discriminating the situations with and without damage and nondamaged infill walls. Validation and calibration of the numerical model was ensured by comparing the numerical frequencies with those obtained from ambient vibration tests. In addition, linear elastic analyses were carried out, using real accelerograms from the Gorkha earthquake to assess and quantify the major differences between the models in terms of inter-storey drifts ratios, inter-storey shear forces and seismic loadings.